Borders of Citizenship and the everyday life of African migrants’ in the city of São Paulo, southeast of Brazil - Fernandes, Caio Silveira (2023)
This paper proposes the notion of the “Borders of Citizenship” to emphasize people and mobility infrastructures (Jung, Buhr, 2021) that mediate citizenship through many places, actors, and social codes of and beyond the State. Thus, based on the concept of relational citizenship (Staheli et al., 2012), I present an Ethnography carried out from 2019 to 2022 in a Cultural Center, founded by African migrants in the city of São Paulo. More specifically, I draw attention to the center’s creation through Mamadou’s trajectory, the owner of the center, to highlight how mobility infrastructures play a decisive role in mediating migrant’s everyday life through many places, actors, and scales expanding their “sustainability of life”, materially and immaterially. I argue that these ordinary spaces are not politically inconsequential for the city or for the migrants.